A PSO-DQ Current Control Scheme for Performance Enhancement of Z-Source Matrix Converter to Drive IM Fed by Abnormal Voltage - Sebtahmadi, Seyed Sina; Azad, Hanieh Borhan; Kaboli, S. Hr. Aghay; Islam, Md. Didarul; Mekhilef, Saad (Institute of Electrical and Electronics Engineers, 2018)
A rotational d-q current control scheme is prepared with the particle swarm optimization-PI controller, which drives an induction motor through an ultra-sparse Z-source matrix converter. To minimize the total size of the system, the lowest feasible values of Z-source elements are calculated by considering both timing and circuit aspects. A meta-heuristic method is integrated with the control system in order to find the optimum coefficients values in a single multimodal problem. Henceforth, the effect of all coefficients in minimizing the THD and balancing the stator current are considered simultaneously. By changing the reference point of magnitude or frequency, the modulation index can be automatically adjusted and respond to changes without heavy computational cost. The focus of this research is on having a reliable and lightweight system with no extensive computing time demand. The proposed scheme is validated by the promising simulation and experimental results.